Modernity and Malaysia settling the Menraq forest nomads - Gomes, Alberto G., 1954- (Modern anthropology of Southeast Asia, 2007)
Bringing together over thirty years of detailed ethnographic research on the Menraq of Malaysia, this book analyses and documents the experience of development and modernization in tribal communities. It traces the transformation of the lives of Menraq resulting from resettlement, development, and various 'civilizing projects'